Perceived Social Acceptance and Peer Status Differentially Predict Adjustment in Youth With and Without ADHD. (January 2014) - McQuade, Julia D.; Vaughn, Aaron J.; Hoza, Betsy; Murray-Close, Dianna; Molina, Brooke S. G.; Arnold, L. Eugene; Hechtman, Lily
Objective: This study extends previous research and examined if the longitudinal relation between self-perceived social acceptance and changes in adjustment was moderated by peer status and ADHD diagnosis.Method: A sample of children with ADHD and a normative comparison group (age 8-13 years) were assessed at baseline and one-year follow-up. Self-perceived social acceptance, peer status, and three areas of adjustment (depression symptoms, aggression/conduct problems, and social skills) were measured.Results: Moderation was found when predicting depression symptoms and aggression/conduct problems. Specifically, in children with ADHD only, higher perceived social acceptance protected against increases in depression symptoms for those with lower peer preference, but predicted greater aggression/conduct problems for those with higher peer preference. There was not evidence of significant moderation for predicting social skills; instead non-ADHD status, greater peer preference, and greater self-perceived social acceptance were each predictive of greater social skills.Conclusion: Results highlight the complex association between positive social self-perceptions and adjustment for children with ADHD and caution against a universal assumption that high self-perceptions are adaptive.